Progress and challenges in designing dynamic in vitro gastric models to study food digestion - Singh, R. Paul (Frontiers in Nutrition, 2024)
Understanding the mechanisms involved in food breakdown in the human gastrointestinal (GI) tract is essential in food digestion research. Research to study food digestion in the human GI tract requires in vivo and in vitro approaches. In vivo methods involving human or animal subjects are often cost-prohibitive and raise ethical concerns. For these reasons, in vitro approaches are becoming more common. Several dynamic in vitro models that mimic one or more components of the GI tract have been developed at various research institutions and by commercial companies. While there is evidence of considerable novelty and innovation in the design of these models, there are many differences among them in how the mechanical breakdown of solid foods is accomplished. In some systems, modulating water pressure is used to achieve peristaltic contractions of the gastric antrum, whereas, in other models, the flexible walls of a gastric chamber are compressed by the movement of rollers or clamps outside the walls of the test chamber. Although much progress has been made in standardizing the biochemical environment appropriate to the food digestion process, there is a lack of standard protocols to measure mechanical forces that result in the breakdown of solid foods. Similarly, no standardized methods are available to evaluate the results obtained from in vitro trials for validation purposes. Due to the large variability in the design features of in vitro models used for food digestion studies, developing consensus-based standards for the mechanical aspects of food breakdown is needed.